Recent Advances in the Synthesis and Stabilization of Nickel and Nickel Oxide Nanoparticles: A Green Adeptness - Muhammad Imran Din; Aneela Rani (International Journal of Analytical Chemistry)
Green protocols for the synthesis of nanoparticles have been attracting a lot of attention because they are eco-friendly, rapid, and cost-effective. Nickel and nickel oxide nanoparticles have been synthesized by green routes and characterized for impact of green chemistry on the properties and biological effects of nanoparticles in the last five years. Green synthesis, properties, and applications of nickel and nickel oxide nanoparticles have been reported in the literature. This review summarizes the synthesis of nickel and nickel oxide nanoparticles using different biological systems. This review also provides comparative overview of influence of chemical synthesis and green synthesis on structural properties of nickel and nickel oxide nanoparticles and their biological behavior. It concludes that green methods for synthesis of nickel and nickel oxide nanoparticles are better than chemical synthetic methods.